Reduced-order damping controller design for power systems via frequency-weighted model reduction - Mudassar, Muhammad; Zulfiqar, Umair; Sreeram, Victor; Liaquat, Muwahida; Haja Mohideen, Ahmad Jazlan (IEEE, 2021)
A damping controller is essential for the smooth operation of power systems. Different types of disturbances result in low-frequency oscillations, which propagate in all the interconnected machines. A safe operation of an interconnected power system requires sufficient damping of these oscillations. Otherwise, there are high chances of blackouts. As the order of the interconnected power system model increases, the analytical controller design procedures result in a high-order controller, which is impractical to implement. In this paper, we demonstrate that the frequency-weighted model order reduction can be used to effectively design a reduced-order loop shaping damping controller. To that end, we design an H-Infinity damping controller for the interconnection of the New England test system (NETS) with the New York power system (NYPS) with an additional constraint of pole-placement. The time-domain simulations of disturbed system with and without controller are performed using MATLAB. Results show that the designed controller successfully removes the low frequency oscillations, maintains synchronism among generators, and guarantees the stability of the power system.